PARENTAL BELIEF ON HPV VACCINATION ACCEPTANCE: A STUDY ON FEMALE STUDENT AT PRIMARY SCHOOL IN SURABAYA - Nasywa, Shofia Ayu Hilda Atha; Wardani, Yuniar Putri; Herawati, Jenny Dwi; Nurbaittrisna, Fatya; Artanti, Kurnia Dwi (Jurnal Biometrika dan Kependudukan, 2025)
Cervical cancer is the second leading cause of cancer-related deaths and one of the major health financing burdens in Indonesia. The Global Cancer Observatory reported 36,633 new cases of cervical cancer in Indonesia in 2020, with mortality rates on the rise. The primary cause, accounting for 99.7% of cases, is the oncogenic human papillomavirus (HPV). HPV vaccination was expanded as a national program through the School Immunization Month in 2023. However, evaluations reveal ongoing parental resistance, preventing vaccination coverage targets from being met. The purpose of this study is to identify related factors to parental perceptions toward the acceptance or rejection of HPV vaccination. This research uses quantitative methods. Data analysis was carried out by displaying quantitative statistical results using the Chi Square SPSS test from 100 respondents. As a result, no association was found between the Health Believe Model (HBM) theory among parents and the vaccination status of elementary school female student aged 11-12 years in Surabaya. There are other factors that may influence the confidentiality of protection against the HPV vaccine, such as misinformation, the influence of social norms, and the level of trust in the government health system. In addition, further research is needed to investigate and explore other factors outside the Health Belief Model theory that may be involved in HPV vaccination coverage.